Some observations and improvements on SMA 6/60 determinations of creatinine - Close-Moll, Madeleine (1972)
Modifications to an earlier SMA 6/60 method for creatinine determinations are reported. The suggested procedure is linear for concentrations up to 15 mg/100 ml, shows no zero drift, and has a satisfactory analytical precision. Effects have been determined upon the analysis for a number of non-creatinine constituents of biological fluids. Recommendations are made for the optimum determination of plasma and urine creatinine.